PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO DAN TOTAL ASSETS TURN OVER TERHADAP PROFITABILITAS PADA PERUSAHAAN FOOD & BEVERAGE - Fifit Fuspitasari; Zurlina Lubis (Fakultas Ekonomi dan Bisnis, Universitas Jayabaya, 2024)
This study aims to analyze the effect of current ratio, Debt To Equity Ratio, Total Assets Turn Over on Profitability listed on the Indonesia Stock Exchange. The population used in this study is the food and beverage manufacturing sub-sector companies. This study retrieves data stored on the Indonesia Stock Exchange from 2018-2022, this study uses quantitative and saturation methods sampling method. The data used is secondary data and uses panel data regression analysis method with the help of the Eviews 12 program to get a comprehensive picture relationship between independent and dependent variables. Based on the results of research, shows that simultaneously Current Ratio, Debt To Equity Ratio, Total Assets Turn Over have a significant effect on Profitability. While some evaluation Curent Ratio has no significant effect on Profitability, Debt To Equity Ratio has no significant effect has a significant effect on Profitability, and Total Assets Turn Over has a significant effect on Profitability. Kata kunci: Current Ratio, Debt To Equity Ratio, Total Assets Turn Over, Profitabilitas